THE EFFICACY AND SAFETY OF DIHYDROPYRIDINE CALCIUM CHANNEL BLOCKERS IN HYPERTENSIVE PATIENTS: AMLODIPINE PLACE - M. V. Lebedeva; V. D. Beketov; N. V. Maltsev; M. E. Safarova (Рациональная фармакотерапия в кардиологии, 2015)
Findings of the main clinical trials of amlodipine in the treatment of arterial hypertension and prevention of fatal and non-fatal cardiovascular events are presented.